European social policy between national and supranational regulation: Posted workers in the framework of liberalized services provision - Werner Eichhorst (Max-Planck-Institut für Gesellschaftsforschung, 1998)
European social policy has two central dimensions: the relation between liberalized market freedoms and social protection, on the one hand, and the distribution of regulatory competencies between the supranational and the national level on the other. The posted workers issue, i.e. the question of which labor law should be applied to workers posted abroad in order to provide services, shows how both dimensions interacted in bringing about a regulatory pattern of national and supranational market-modifying regulation that might be typical for the restricted potential of social regulation in the Single European Market. In several member states, especially France, Austria and Germany, market-modifying measures were introduced according to the pre-established European and international law and the judgments of the European Court of Justice. However, the substance of these diverging regulatory acts depended heavily on many institutional and political factors in each member state. In fact, national regulations pre-empted the effects of subsequent supranational market modification, making it possible for a European directive on posted workers to be adopted after many years of deadlock in the Council of Ministers. But this directive allows national regulations to remain in place with hardly any changes, and it safeguards national autonomy regarding decisions on the substance of binding labor law to be applied to posted workers. The supranational measure can be described as an umbrella that protects national market modification by means of European law without interfering with the institutional arrangements or the political disputes in the member states. – – Europäische Sozialpolitik befindet sich heute in einem doppelten Spannungsverhältnis: Auf der einen Seite geht es hierbei um die Beziehung zwischen den Marktfreiheiten des Europäischen Binnenmarktes und dem Prinzip des sozialen Schutzes. Auf der anderen Seite wird die Frage der Verteilung der Regulierungskompetenzen zwischen der europäischen und der nationalen Ebene berührt. Die politische Behandlung der Entsendeproblematik, also der rechtlichen Stellung entsandter Arbeitnehmer im Rahmen der Dienstleistungsfreiheit, zeigt, wie diese beiden Dimensionen Europäischer Sozialpolitik interagierten und ein Regulierungsmuster hervorbrachten, das typisch für die beschränkten sozialpolitischen Regulierungsmöglichkeiten im Binnenmarkt sein könnte: Einerseits schufen mehrere Mitgliedstaaten, unter ihnen Frankreich, Österreich und Deutschland, im Rahmen des vorhandenen europäischen und internationalen Rechts sowie der Rechtsprechung des Europäischen Gerichtshofes nationale Entsendegesetze mit unterschiedlicher Gestalt. Andererseits konnte schließlich vor dem Hintergrund dieser einzelstaatlichen Marktbeschränkungen eine europäische Entsenderichtlinie verabschiedet werden, die bereits seit mehreren Jahren auf supranationaler Ebene behandelt worden, aber lange Zeit aufgrund von Interessengegensätzen blockiert gewesen war. Diese Richtlinie schirmt die nationalen Regelungen ab, welche den rechtlichen und ökonomischen Effekt der supranationalen Regulierung vorweggenommen hatten, und verteidigt sie gegenüber einer Infragestellung rechtlicher oder politischer Art, ohne aber in die institutionelle Struktur arbeitsrechtlicher Vorschriften und die jeweiligen politischen Konstellationen in den Einzelstaaten einzugreifen.
Keywords: 300; EU-Sozialpolitik; Mindestlohn; Internationale Arbeitsmobilität; EU-Binnenmarkt; Niederlassungsrecht; EU-Staaten